Faktor-faktor yang berhubungan dengan pernikahan usia dini pada remaja usia 15-18 tahun - Apriyadi Apriyadi; Dessy Hermawan; Lolita Sary (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Sociocultural factors in practices of early marriage in 15–18 years old adolescentBackground: Early marriages have a negative impact on health, both for mothers from pregnancy to childbirth and infants due to imperfect reproductive organs. Immature reproductive organs cause women who get married early at risk. In Gunung Labuhan Village, Sungkai Selatan District in 2017 there were early marriage with 27 people married at less than 18 years old.Purpose: To identify Sociocultural factors in practices of early marriage in 15–18 years old adolescentMethod: A quantitative, case control research design. The population in this study were all adolescents in Gunung Labuhan Village, Sungkai Selatan District, North Lampung Regency in 2018 with 341 people with 27 cases of early marriage and 27 controls. Statistical tests using the chi square test.Results: There is a relationship between education, parental education, occupation, parental occupation, income with early marriage in Gunung Labuhan Village, South Sungkai District, North Lampung Regency 2018. Suggestions are expected to socialize the time of marriage and the impact of early marriage through counseling and using language that is easily understood to children who entering the age of young women and parents.Conclusion: that the average age is 16.22, the standard deviation is 0.80, the range is 15-17 years, the basic education is 18 (66.7%) respondents, the job is to work 20 (74.1%) the respondents, the parents' work is not permanent 17 (63.0%) respondents, low income 14 (51.9%). The relationship between early marriage and education (p-value 0.014), the relationship between early marriage and parental education (p-value 0.028), the relationship between early marriage and work (p-value 0.006), the relationship between early marriage and parental occupation (p-value 0.029), the relationship between early marriage and income (p-value 0.049).Keywords: Sociocultural factors; Practices of early marriage; Adolescent (15–18 years old)Pendahuluan: Pernikahan usia dini berdampak buruk pada kesehatan, baik pada ibu dari sejak hamil sampai melahirkan maupun bayi karena organ reproduksi yang belum sempurna. Belum matangnya organ reproduksi menyebabkan perempuan yang menikah usia dini berisiko. Di Desa Gunung Labuhan Kecamatan Sungkai Selatan pada tahun 2017 terdapat pernikahan usia dini dengan jumlah 27 jiwa menikah di usia kurang dari 18 tahunTujuan: Diketahui faktor-faktor yang berhubungan dengan pernikahan usia dini pada remaja usia 15-18 tahunMetode: Penelitian kuantitatif dengan desain penelitian case control. Populasinya seluruh remaja di Desa Gunung Labuhan Kecamatan Sungkai Selatan Kabupaten Lampung Utara 2018sebanyak 341 orang dengan jumlah kasus pernikahan dini 27 orang, dan 27 kontrol.Uji statistik menggunakan uji chi square.Hasil: Bahwa usia dengan rata – rata 16,22, standar devisiasi 0,80, rentang 15-17 tahun, pendidikan dasar 18 (66,7%) responden, pekerjaan dengan bekerja 20 (74,1%) responden, pekerjaan orang tua tidak tetap 17 (63,0%) responden, pendapatan rendah 14 (51,9%). Hubungan antara pernikahan dini dengan pendidikan (p-value 0,014), hubungan antara pernikahan dini dengan pendidikan orang tua (p-value 0,028), hubungan antara pernikahan dini dengan pekerjaan (p-value 0,006), ubungan antara pernikahan dini dengan pekerjaan orang tua (p-value 0,029), hubungan antara pernikahan dini dengan pendapatan (p-value 0,049).Simpulan: Ada hubungan pendidikan, pendidikan orang tua, pekerjaan, pekerjaan orang tua, pendapatan dengan pernikahan usiadini di Desa Gunung Labuhan Kecamatan Sungkai Selatan Kabupaten Lampung Utara 2018. Saran diharapkan mensosialisasikan waktu pernikahan dan dampak pernikahan dini melalui penyuluhan dan menggunakan bahasa yang mudah dipahami kepada anak yang memasuki usia remaja putri dan orang tua.